The Phenomenon Of Child Marriage During The Covid-19 Pandemic From A Legal Sociological Perspective In The Kota Timur Sub-District, Gorontalo City - Nadia Buwono (Estudiante Law Journal, 2019)
The purpose of this study is to analyze the phenomenon of child marriage during the Covid-19 pandemic from the legal sociological perspective and to find out how the KUA (Religious Affairs Office) handles cases of child marriage during the Covid-19 pandemic in Gorontalo City and to find out the factors that lead to child marriages during the Covid-19 pandemic. The Ministry of PPPA (Women Empowerment and Child Protection) reported that during the Covid-19 pandemic the number of child marriages increased, especially in Kota Timur Sub-District. So, this needs to be considered by the local authorities, namely the KUA, because the KUA plays an important role in minimizing the number of child marriages. Based on these problems, the authors were encouraged to research to find out the picture of child marriage in the KUA of Kota Timur Sub-District, what efforts have been made by the KUA of Kota Timur Sub-District in handling the number of child marriages during the Covid-19 pandemic, what obstacles are the KUA of Kota Timur Sub-District encounters in handling with child marriages. Factors that caused child marriages were habit factors, economic factors, matchmaking factors, and low education factors. The reason was media freedom, weak parental supervision so an undesirable situation occurred, namely pregnancy out of wedlock. In this case, it has an impact on being forced to marry so that there is a request for dispensation to be able to marry at an early age.